Pengaruh Pelaksanaan Program Kartu Keluarga Sejahtera Terhadap Kesejahteraan Masyarakat Desa Watampanua Kecamatan Pammana Kabupaten Wajo - Qadar, Jamal; Maspawati Maspawati; Upe Alnamira (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Poverty and unemployment are phenomena and social problems that are continuously being studied and are of concern to the central government of Indonesia as a developing country which is still in the process of development, especially in the economic field. Therefore, one of the programs established by the government to reduce the burden on society in meeting the needs of the poor is the Prosperous Family Card Program (KKS). The type of research used in this research is associative survey research, namely a research formulation that is asking the relationship between two or more variables, with the main data collection technique being a questionnaire with a quantitative approach method. The quantitative research method is a type of research whose specifications are systematic, planned and clearly structured from the start to the creation of the research design. The implementation of the Prosperous Family Card Program in Watampanua Village, Pammana District, Wajo Regency is included in the good category, as well as the welfare of the people in Watampanua Village, Pammana District, Wajo Regency, which is included in the good category. Meanwhile, the influence of the Implementation of the Prosperous Family Card Program on Community Welfare in Watampanua Village, Pammana District, Wajo Regency has a strong and positive influence.